2013
DOI: 10.1007/s10709-013-9726-5
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and structural chromosome variation in the swarm-founding wasp Metapolybia decorata Gribodo 1896 (Hymenoptera, Vespidae)

Abstract: The Neotropical Polistinae wasps are diverse in taxonomy, social behavior, and nesting founding characteristics. Although some species in this group have been used as models for studies on wasp's biology, they are poorly known in terms of cytogenetics. Here we reported an intraspecific numerical-structural chromosome variation in the swarm-founding wasp Metapolybia decorata from the Brazilian Atlantic Rainforest using conventional and molecular cytogenetic techniques. The observed structural chromosome change … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 27 publications
4
20
0
Order By: Relevance
“…in the most prolific clades of parasitoid Hymenoptera, and perhaps in the latter group in general [Gokhman et al, 2014a]. Together with detection of the apparently parallel loss of the above-mentioned repeat in the single studied member of the superfamily Vespoidea [Menezes et al, 2013], our results suggest that telomere structure can be much more variable among different hymenopteran taxa than it was supposed just a few years ago.…”
Section: Phylogenetic Implications Of Karyotypic Study Of Parasitoid supporting
confidence: 61%
“…in the most prolific clades of parasitoid Hymenoptera, and perhaps in the latter group in general [Gokhman et al, 2014a]. Together with detection of the apparently parallel loss of the above-mentioned repeat in the single studied member of the superfamily Vespoidea [Menezes et al, 2013], our results suggest that telomere structure can be much more variable among different hymenopteran taxa than it was supposed just a few years ago.…”
Section: Phylogenetic Implications Of Karyotypic Study Of Parasitoid supporting
confidence: 61%
“…It could indicate a modal pattern in the genus, but a higher number of species should be studied. This pattern is also recurring in other Hymenoptera, such as parasitic and social wasps (Gokhman et al 2014;Menezes et al 2013) and ants (Imai et al 2001). However, reports of multiple 18S rDNA signals were also described in Hymenoptera, as in Partamona (Meliponini) (Brito et al 2005) and some parasitoid wasps (Paladino et al 2013;Gokhman et al 2014).…”
Section: Resultsmentioning
confidence: 75%
“…A few years later, Gokhman et al () also showed absence of this repeat in several superfamilies of parasitoid Hymenoptera including Chalcidoidea. Futhermore, Menezes et al () and Menezes et al () have demonstrated absence of the (TTAGG) n motif in most aculeate Hymenoptera and independent reappearance of this repeat in the families Formicidae and Apidae. Nevertheless, in contrast to Apocrita (=Parasitica + Aculeata), presence of the TTAGG telomeric repeat in the only other existing suborder of this group, i.e., Symphyta, was not investigated until the last years.…”
Section: Telomere Structure In the Class Insectamentioning
confidence: 98%
“…Recent research on insect telomeres has revealed several examples of heterogeneity for presence/absence of the (TTAGG) n motif within, e.g., Hemiptera: Heteroptera (Angus, Jeangirard, Stoianova, Grozeva, & Kuznetsova, ; Chirino, Dalíková, Marec, & Bressa, ; Golub, Golub, & Kuznetsova, , , ; Grozeva, Kuznetsova, & Anokhin, ; Kuznetsova, Grozeva, & Anokhin, ; Pita et al, ) and Hymenoptera (Gokhman, Anokhin, & Kuznetsova, ; Gokhman & Kuznetsova, ; Menezes, Bardella, Cabral‐de‐Mello, Lucena, & Almeida, ; Menezes et al, ), and even between closely related species of the order Odonata (Kuznetsova, Maryańska‐Nadachowska, Shapoval, Anokhin, & Shapoval, ). Insects that lack canonical telomeric repeats probably constitute about 10%–15% of all animal species (Mason et al, ).…”
Section: Introductionmentioning
confidence: 99%